A grounding method of OCS pillar foundation based on conductive concrete - CHANG Zhanning; ZHANG Yiping; YU Shudan; XIE Zining; LU Weinan; CHENG Hongbo (机车电传动)
A grounding method of OCS pillar foundation based on conductive concrete was proposed to solve the grounding problem of traction power supply system in areas with high soil resistivity. The proportioning of materials for conductive concrete was optimized from two aspects: mechanical strength and conductivity, and the composite conductive material composed of 20% graphite + 2.5% steel fiber was selected. By analyzing the natural grounding scheme and effect of conductive concrete OCS pillar foundation, it was found that scheme could reduce the grounding resistance by 73.16%. If the adjacent foundations were connected, it could meet the requirements of grounding resistance of traction power supply system. The electrothermal characteristics of conductive concrete foundation under lightning impulse were analyzed, and it was found that the temperature rise of conductive concrete OCS pillar foundation was small. The internal temperature distribution was uniform, and it was not easy to be affected by structural stress. The proposed grounding method of traction power supply system based on conductive concrete only needs to replace the ordinary concrete with conductive concrete during construction, which is simple and convenient to implement. It provides a new method for the grounding of electrified railway in areas with high soil resistivity.